PENGARUH SUPLEMENTASI HIDROLISAT BULU AYAM DAN MINERAL ORGANIK TERHADAP KADAR VFA SERTA NH3 PADA CAIRAN RUMEN SAPI - Kusuma, Dhimas Angger; Sutrisna, Rudy; ., Muhtarudin (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This study aimed: 1) to optimalize the using of agroindustry by product through the hidrolyzedpoultry feather and organic mineral supplementation in ration to increase the digestion of cows; 2) todetermine the best effect of hidrolyzed poultry feather and organic mineral supplementation level toVFA and NH3 value in rumen liquid of cows.This study was conducted in August until October 2013 located in the Stall of Animal HusbandryDepartment, Faculty of Agriculture Lampung University. The analysis of feed stuff, VFA and NH3was conducted in Laboratory of Animal Feed, Animal Husbandry Department. This study used LatinSquare Design with 3 treatments and 3 replications. R0 = Bassal Ration, R1 = Bassal Ration + 3%hidrolyzed poultry feather, R2 = R1 + macro-organic Mineral (0,5% organic Ca, 0,04% organic Mg)and micro-organic Mineral (40 ppm organic Zn, 10 ppm organic Cu, 0,10 ppm organic Se, dan 0,30organic Cr).The data obtained were tested by analysis of variance ( ANOVA ) and was continued by usingLeast Significant Different (LSD) on significant level 5% and or 1%. The result of this study showedthat: the hidrolyzed poultry feather and macro-organic mineral supplementation (0,5% organic Ca,0,04% organic Mg) and micro-organic Mineral (40 ppm organic Zn, 10 ppm organic Cu, 0,10 ppmorganic Se, dan 0,30 organic Cr) were not significantly different (P>0,05) to VFA and NH3 value inrumen liquid of cows.